Circumcising daughters in Nigeria: To what extent does education influence mothers’ FGM/C continuation attitudes? - Josephine Akua Ackah; Patience Ansomah Ayerakwah; Kingsley Boakye; Bernard Afriyie Owusu; Vincent Bio Bediako; Millicent Gyesi; Edward Kwabena Ameyaw; Francis Appiah (PLOS Global Public Health, 2022)
Education has been adjudged as an important behavioural change intervention and a key player in combating Female Genital Mutilation/Cutting (FGM/C). An assumed pathway is that it influences FGM/C attitudes. However, empirical evidence that explores this assumption is scarce. Hence, our study examines whether the associative effect of FGM/C continuation attitudes on circumcision of daughters is influenced by the level of a mother’s education in Nigeria. We extracted data from the 2018 Nigeria Demographic and Health Survey (NDHS). The study focused on youngest daughters that were born in the last five years preceding the survey. A sample of 5,039 children with complete data on variables of interest to the study were analysed. The main outcome variable for this study is “circumcision among youngest daughters”. The key explanatory variables were maternal “FGM/C continuation attitudes” and “education”. At 95% confidence interval, we conducted a two-level logistic regression modelling and introduced interaction between the key independent variables. In the study’s sample, the prevalence of FGM/C was 34%. It was lower for daughters whose mothers had higher education (12%) and believe FGM/C should discontinue (11.1%). Results from the multivariate analysis show statistically significant odds of circumcision for a daughter whose mother has had higher education and believes FGM/C should discontinue (OR-0.28, 95%CI: 0.08–0.98). For women who believe FGM/C should discontinue, the probability of daughter’s circumcision reduced by 40% if the mother has attained higher education. Among those who believe FGM/C should continue, the probability of daughter’s circumcision worsened if the mother had attained higher education (64%), however, this result was influenced by mothers’ experience of circumcision. Education influences FGM/C attitudes, nonetheless, women’s cutting experience can be a conduit for which the practice persists. Promoting female education should be accompanied by strong political commitment towards enforcing laws on FGM/C practice.